2007
DOI: 10.1051/vetres:2007035
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of proinflammatory cytokines in mammary glands of sows suggests an association between clinical mastitis and local production of IL-1beta, IL-6 and TNF-alpha

Abstract: -Twelve healthy primiparous sows received intramammary inoculation with Escherichia coli (serotype O127) during the 24-h period preceding parturition. Mammary gland biopsy samples were taken immediately before inoculation (0 h) and from the inoculated and the contralateral noninoculated glands 24 h after inoculation. The analyses of interleukin-1 beta (IL-1β), IL-6, IL-8, and tumor necrosis factor alpha (TNF-α) by immunohistochemistry revealed that the production of these proinflammatory cytokines significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…We found that pre-incubation with L. johnsonii L531 restricts E. coli -induced NLRP3 inflammasome activation, including the expression of receptor protein NLRP3, the adaptor protein ASC, the effector caspase-1 p10 and the release of Il-1β and Il-18 . Consistent with other studies in vivo and the microarray analysis results [ 48 , 49 , 50 , 51 ], the expression of cytokines and chemokines, such as Il-6 , Il-8 , Tnf-α , and Cxcl2 was up-regulated after E. coli challenge, whereas this increase was attenuated by pre-incubation with L. johnsonii L531. L. johnsonii L531 inhibits the activation of NLRP3 inflammasome during E. coli infection.…”
Section: Discussionsupporting
confidence: 91%
“…We found that pre-incubation with L. johnsonii L531 restricts E. coli -induced NLRP3 inflammasome activation, including the expression of receptor protein NLRP3, the adaptor protein ASC, the effector caspase-1 p10 and the release of Il-1β and Il-18 . Consistent with other studies in vivo and the microarray analysis results [ 48 , 49 , 50 , 51 ], the expression of cytokines and chemokines, such as Il-6 , Il-8 , Tnf-α , and Cxcl2 was up-regulated after E. coli challenge, whereas this increase was attenuated by pre-incubation with L. johnsonii L531. L. johnsonii L531 inhibits the activation of NLRP3 inflammasome during E. coli infection.…”
Section: Discussionsupporting
confidence: 91%
“…Inflammation response of periparturient sows after inoculation of porcine mammary gland with different potential mastitis-causing E. coli strains specified a dominant role of that pathogen species in CM [ 10 ]. The development of clinical symptoms of CM in the sow was suggested to be associated with a locally increased production of pro-inflammatory cytokines such as interleukin 1-beta (IL1-beta), IL6, IL8, and tumor necrosis factor-alpha (TNF-alpha) in response to intramammary E. coli infection [ 10 , 11 ]. Additionally, the time of infection of the mammary gland relative to parturition and the number of circulating neutrophils at the time of infection were shown to influence the development of clinical CM in the sow [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the licorice‐treated groups did not respond to the increase in TNF‐α mRNA, which was possibly induced by the SRBC sensitization. IL‐1β, IL‐6 and TNF‐α are known to be inflammation‐related cytokines (Zhu et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the licorice-treated groups did not respond to the increase in TNF-a mRNA, which was possibly induced by the SRBC sensitization. IL-1b, IL-6 and TNF-a are known to be inflammation-related cytokines (Zhu et al 2007). The expression of IL-1b and IL-6 in the licorice-treated group showed relatively lower levels compared with those in the control group, although these differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%